Feasibility Of Organic Rankine Cycle (Orc) Wıth Waste Heat Recovery (مجلة العلوم الشاملة, 2025)
The present study focused on the feasibility of Organic Rankine Cycle (ORC) using waste heatrecovery. The waste heat covered from glass factory. The working fluid in the cycle wereIsobutane. Thermodynamic model of the system was derived and validated for performanceprediction. The validated thermodynamic model is used to optimize the operation of the smallORC in waste heat recovery application. The temperature which recovered and mass flow ratewere 155 ºC and 27 kg/s respectively. The power output of double stage turbines was 8370 kW.The payback period 2.5 years. It is concluded from the study that recovering the waste heat byway of ORCs is technically and economically feasible. As recycled energy, waste heat has thesame advantages as renewable energy.